Pengaruh Adopsi Artificial Intelligence, Kualitas Analisis SWOT, dan Strategi Diferensiasi Terhadap Market Positioning pada Koffie Kawan Bandung: Studi Kasus Koffie Kawan Bandung - Muhammad Alfin Alfarizi; Mario Maulana Wardhana; Siska Ameli; Mega Sakova (Indo Publishing, 2026)
This study examines the direct effects of Artificial Intelligence (AI) Adoption, SWOT Analysis Quality, and Differentiation Strategy on the Market Positioning of Koffie Kawan Bandung. The three constructs were specified as parallel independent variables with direct paths to Y. An explanatory quantitative design was employed using survey data from 43 customers selected through purposive sampling. The instrument consisted of 32 Likert-scale items. All constructs were reliable, with Cronbach's Alpha values ranging from 0.847 to 0.860. The main multiple-regression model produced R = 0.910, R² = 0.827, and adjusted R² = 0.814, and was statistically significant (F = 62.330; p < 0.001). Partially, AI Adoption had a positive and significant effect (B = 0.319; β = 0.310; p = 0.003), SWOT Analysis Quality had a positive but non-significant effect (B = 0.111; β = 0.109; p = 0.428), and Differentiation Strategy had the strongest positive and significant effect (B = 0.559; β = 0.576; p < 0.001). The three paired simultaneous models were also significant: X1 + X2 (F = 54.871; R² = 0.733), X1 + X3 (F = 94.014; R² = 0.825), and X2 + X3 (F = 71.693; R² = 0.782), all with p < 0.001. The findings indicate that differentiation is the most immediate driver of market position, while AI strengthens positioning when translated into relevant marketing decisions and customer value.